2016
DOI: 10.1111/anec.12343
|View full text |Cite
|
Sign up to set email alerts
|

Deceleration Capacity of Heart Rate Predicts Arrhythmic and Total Mortality in Heart Failure Patients

Abstract: DC predicts both SCD and TM. DCsgn avoids the negative values, improving the method in a nonstatistical important level.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 28 publications
1
21
0
1
Order By: Relevance
“…In a study by Arsenos et al, DC was found to be an independent predictor of sudden cardiac death. 19 In our previous study, patients with acute exacerbation of COPD with concomitant ventricular arrhythmias showed an association with reduced DC, which suggests its value as an indicator of autonomic dysfunction. 20 A recent study also found that DC can help stratify COPD patients based on their risk of arrhythmias.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…In a study by Arsenos et al, DC was found to be an independent predictor of sudden cardiac death. 19 In our previous study, patients with acute exacerbation of COPD with concomitant ventricular arrhythmias showed an association with reduced DC, which suggests its value as an indicator of autonomic dysfunction. 20 A recent study also found that DC can help stratify COPD patients based on their risk of arrhythmias.…”
Section: Introductionmentioning
confidence: 86%
“…Arsenos et al validated the application of DC for predicting the risk of arrhythmias in patients with heart failure; they found that DC ≤3.352 ms was significantly associated with increased incidence of arrhythmias. 19 Buzea et al further evaluated the ability of DC to predict the development of arrhythmias in COPD patients; they also found a significant correlation between DC and the incidence of arrhythmias. 21 Based on the results of ROC curve analysis in our study, DRs were found to be a robust predictor of supraventricular and ventricular arrhythmias.…”
Section: Copdmentioning
confidence: 99%
“…In a recent systematic review, HRT showed a consistent predictive value for cardiac death and arrhythmic events (Disertori, Mase, Rigoni, Nollo, & Ravelli, 2016). DC has been shown to be an independent predictor of both SCD and total mortality (Arsenos et al, 2016). DC can be interpreted as a global measure of heart rate deceleration as it is an integral measure of all deceleration-related periodic components of the heart rate over a 24-hr period (Bauer et al, 2009).…”
Section: Selected Parametersmentioning
confidence: 99%
“…DC can be interpreted as a global measure of heart rate deceleration as it is an integral measure of all deceleration-related periodic components of the heart rate over a 24-hr period (Bauer et al, 2009). DC has been shown to be an independent predictor of both SCD and total mortality (Arsenos et al, 2016). However, as ventricular arrhythmias can be considered a coincidence of circumstances, we hypothesize that a global measure of autonomic function, as DC, could yield a higher predictive value than a rather specific measure related to VPBs, as HRT.…”
Section: Selected Parametersmentioning
confidence: 99%
“…A variety of other noninvasive indices from 12‐lead ECG, SAECG and 24‐hour electrocardiography have been suggested, although results were not always consistent; such ECG‐indices included wide or fragmented QRS complex, prolonged QTc interval, nonsustained VT of ≥10 QRS complexes, baroreflex sensitivity or inverse spatial QRS‐T angle (Goldberger et al., ; Huikuri et al., ). Lastly, indices of autonomic function, such as reduced heart rate variability (Arsenos et al., ; Huikuri et al., ), abnormal heart rate turbulence (HRT) or deceleration capacity (Arsenos et al., ), have been widely explored but results have once more been ambiguous (Goldberger, Subačius, Patel, Cunnane, & Kadish, ). It should be noted that autonomic nervous system dysfunction indices have been related more with nonsudden cardiac mortality (Goldberger et al., ; Hayano et al., ).…”
Section: The Multifactorial Approachmentioning
confidence: 99%